2012
DOI: 10.1364/ao.51.008848
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-front tilt for short-wavelength lasing by means of traveling-wave plasma-excitation

Abstract: Generation of coherent short-wavelength radiation across a plasma column is dramatically improved under traveling-wave excitation (TWE). The latter is optimized when its propagation is close to the speed of light, which implies small-angle target-irradiation. Yet, short-wavelength lasing needs large irradiation angles in order to increase the optical penetration of the pump into the plasma core. Pulse-front back-tilt is considered to overcome such trade-off. In fact, the TWE speed depends on the pulse-front sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Considering the high photon energies of 103 eV or λ = 12 nm, the interaction with any material can efficiently lead to secondary electrons and photoemission. The source and its working principle are described in detail elsewhere [6][7][8][9][10][11][12].…”
Section: Extreme Ultraviolet Sourcementioning
confidence: 99%
“…Considering the high photon energies of 103 eV or λ = 12 nm, the interaction with any material can efficiently lead to secondary electrons and photoemission. The source and its working principle are described in detail elsewhere [6][7][8][9][10][11][12].…”
Section: Extreme Ultraviolet Sourcementioning
confidence: 99%
“…A partial turnaround to such trade-off was introduced with transient collisional excitation (TCE 3 ), i.e. using two drive pulses, and carrying out traveling-wave excitation (TWE), as explained in detail previously 4 . TWE aims to achieve the speed matching condition.…”
Section: Introductionmentioning
confidence: 99%
“…Nilsen et al 8 have done a detailed gain length study of Mo plasma-laser with the traveling-wave excitation (TWE) 18 , and showed that without the traveling wave color-2 showed a weak gain. The use of the traveling-wave setup does increase the output of the color-2 in Mo by two orders of magnitude and is essential for observing strong lasing on this line.…”
Section: Introductionmentioning
confidence: 99%